Individual differences provide a nuanced understanding of the contributions of age, experience, and level played to superior perceptual-cognitive-motor skill - Morris-Binelli, Khaya; Westbrook, Minerva A.; Piggott, Benjamin; Müller, Sean; Chivers, Paola (Frontiers in Psychology, 2025)
Theories of expertise either predict superior performance is due to monotonic and progressive exposure to a domain task or due to non-linear exposure to a domain. The aim of this study was to explore the predictions of these theories by use of an individual differences approach to investigate how age, experience, and level played within a sample of athletes with high expertise contributes to superior perceptual-cognitive-motor skill. Twenty-seven players sampled from junior rugby union high-performance pathways and professional rugby union teams in Australia completed an in-situ perceptual-cognitive-motor test involving four attackers and three defenders. Participants were presented with scenarios representative of a typical game and had to decide whether, and who, to pass the ball, execute the pass, or run with the ball. Performance was scored based upon an expert coach rating scale. Results indicated significant individual differences were more pronounced for decision-making, than for motor execution components of the task. Superior decision-making was not dependent solely upon greater experience in playing rugby union, nor age or level played. Further, superior decision-making was not solely dependent upon those participants who specialized in positional play during the typical game scenarios. Findings indicate that theories of expertise may need to accommodate that prolonged exposure to a domain does not provide a complete explanation of expert performance and that the capability to make effective decisions is highly individualized.